2021
DOI: 10.2147/opth.s283888
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcomes of Implantable Collamer Lens Followed by Excimer Laser Enhancement (“Bioptics”) in the Treatment of High Myopic Astigmatism

Abstract: Purpose Describe three-year outcomes of spherical implantable Collamer lens (ICL) followed by excimer laser enhancement (bioptics) in eyes with high myopic astigmatism. Patients and Methods Retrospective case series of thirty-four cases that underwent bioptics enhancement at the Johns Hopkins Wilmer Eye Institute. All eyes had a preoperative sphere of −6.00 D or more with a cylinder of at least 2.00 D. Uncorrected and corrected distance visual acuity (UDVA and CDVA), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“… 2 Bioptics strives to address this limitation by distributing the large refractive correction between a corneal laser ablation and an implantable posterior chamber phakic intraocular lens. 3 , 4 With the approval of the Visian Toric Implantable Collamer Lens (STAAR Surgical, Monrovia, CA, USA) (Toric ICL) in 2018, patients with high myopic astigmatism now have an alternative option that decreases the need for a second surgery. Initial data concerning Toric ICLs shows promise for improved visual acuity with a safe and predictable outcome.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Bioptics strives to address this limitation by distributing the large refractive correction between a corneal laser ablation and an implantable posterior chamber phakic intraocular lens. 3 , 4 With the approval of the Visian Toric Implantable Collamer Lens (STAAR Surgical, Monrovia, CA, USA) (Toric ICL) in 2018, patients with high myopic astigmatism now have an alternative option that decreases the need for a second surgery. Initial data concerning Toric ICLs shows promise for improved visual acuity with a safe and predictable outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results demonstrating excellent long-term safety, predictability, and efficiency in addressing high myopic astigmatism were provided by Jabbour et al, who reported 3-year outcomes of spherical ICL followed by bioptics in eyes with high myopic astigmatism. 14 A recent analysis of the results of bioptics procedures for correction of high myopia (À16.50 to À28.00 D) by Brar et al revealed that most of the ICLs were the V4c model, which already came with a central port, and that the technique used for enhancement bioptics procedures was small-incision lenticule extraction. 10 Ten (67%) of the 15 eyes included in the study were within ± 0.50 D, whereas all eyes were within ± 1.00 D of spherical equivalent correction.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results demonstrating excellent long-term safety, predictability, and efficiency in addressing high myopic astigmatism were provided by Jabbour et al, who reported 3-year outcomes of spherical ICL followed by bioptics in eyes with high myopic astigmatism. 14…”
Section: Discussionmentioning
confidence: 99%